2008
DOI: 10.1007/s11199-008-9527-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mothers’ and Fathers’ Relationships with Sons Versus Daughters: Links to Adolescent Adjustment in Mexican Immigrant Families

Abstract: Drawing on ecological and gender socialization perspectives, this study examined mothers' and fathers' relationships with young adolescents, exploring differences between mothers and fathers, for sons versus daughters, and as a function of parents' division of paid labor. Mexican immigrant families (N = 162) participated in home interviews and seven nightly phone calls. Findings revealed that mothers reported higher levels of acceptance toward adolescents and greater knowledge of adolescents' daily activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 42 publications
5
133
3
Order By: Relevance
“…The results contradict the notion of same-sex socialization behaviors in parents, in which fathers were said to be more likely to be involved in their son's development (Updegraff, et al, 2009). Instead, fathers in this study take more measures to encourage, support and assist their daughter's school-related activities.…”
Section: Differential Treatment Of Single Fathers and Single Mothers contrasting
confidence: 99%
See 2 more Smart Citations
“…The results contradict the notion of same-sex socialization behaviors in parents, in which fathers were said to be more likely to be involved in their son's development (Updegraff, et al, 2009). Instead, fathers in this study take more measures to encourage, support and assist their daughter's school-related activities.…”
Section: Differential Treatment Of Single Fathers and Single Mothers contrasting
confidence: 99%
“…In comparison to paternal parenting, mother parenting posits greater influence over the adolescent's later development (McKinney & Renk, 2008). The uniqueness of mother-adolescent relationship is illustrated in a way that would promote good outcomes in children, such as high academic achievement and reducing adolescents' risky behaviors (Updegraff et al, 2009). Given different family arrangements and quality of care provided by single fathers and mothers, we predicted different parenting goals and practices in these family settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers, on the other hand, were reported to be more accepting of young adolescents (Updegraff, Delgado, & Wheeler, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Our research focused on mother-adolescent dyads because immigrant as well as nonimmigrant mothers were found to spend more time with adolescents than fathers and they often have deeper insights into the lives of their offspring (Dubas and Gerris 2002;Updegraff et al 2009). Furthermore, in a recent study, adolescents reported on maternal and paternal warmth over a 5-year period (Rodríguez et al 2013).…”
Section: Mother-adolescent Agreementmentioning
confidence: 99%